Bases moleculares do sistema Rh e suas aplicações em obstetrícia e medicina transfusional - Nardozza, Luciano Marcondes Machado [UNIFESP] (2010)
The Rh system is the most polymorphic and immunogenic for all blood group systems. Currently more than 49 antigens were identified with five major antigens D, C, c, E, e. Knowledge of the Rh system's molecular basis, since its first cloning 17 years ago, allowed to understand the mechanism of Rh-negative phenotype and the variants of antigens as RHD and RHCE. Deletions, gene rearrangements and insertions are the main mutations. In Caucasians the primary mechanism of Rh-negative phenotype is the complete RHD gene deletion, while in African descendants it is the presence of pseudogene and gene RHDψ hybrid RHD-CE (4-7)-D. The authors analyze the structure of the Rh complex in red cells, molecular basis of the Rh system, mechanisms of Negativity RHD and weak and incomplete expression of RHD.